Burnout Syndrome in Sport (Research, Society and Development, 2022)
Through cataloged data from studies already carried out, it was seen that Burnout has a set of symptoms for the syndrome. Those are assessed in three dimensions for its diagnosis within the labor and sporting scope. Therefore, it was visualized in the studies by Gustafsson that among 980 athletes from 58 different modalities, a considered part of them suffered with levels below the moderate of symptoms of the Burnout Syndrome. According to Goodger, 73 percent of the studies collected were from women who showed high levels of anxiety, tension and stress. It was also noted that part of the characteristics of Burnout Syndrome are physical and psychological problems that influence the physiology and may even develop symptoms of overtraining syndrome, preventing athletes from performing their potential in certain competitions or not progressing accordingly in training.